Spiritual Harmony: The Practice of Living the Qur’an and Hadith Through the Prayer Wirid Tradition in West Sulawesi - M. Dalip; Muhammad Yunan; Abdul Gaffar Haris (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2023)
This article seeks to explore the meanings ascribed to the recitation of wirid prayer within Muslim communities in West Sulawesi. Wirid prayer represents an important aspect of Muslim devotional practice, extending beyond a simple series of prayers or dhikr to encompass various interpretations within the local cultural context. This study employs a qualitative approach to examine the relevance and significance of wirid recitations in the daily lives of the people in West Sulawesi, and how these practices shape their religious identity. The study identifies three primary meanings associated with the practice of wirid prayer. First, the recitation is understood as a form of spiritual healing, reflecting the community's belief in its ability to provide both physical and mental well-being. Secondly, the recitation is seen as Istiadzah, a form of protection believed to shield individuals from potential threats, both physical and non-physical. This demonstrates the community’s perception of the efficacy of wirid as a safeguard. Lastly, the recitation of wirid prayer is perceived as a jampi or mantra, another form of protection believed to safeguard individuals from various dangers.